Efektivitas Model Bermain Peran Terhadap Keterampilan Bercerita Siswa Sekolah Dasar - Sunardi Sunardi (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
The aim of this study was to investigate whether the role play teaching model had an effect on students’ story telling skill in primary schools in Salatiga. This study was experimental research. A T-test on the pre-test data showed that the mean of the experimental group was 18.94, whereas the mean of the control group was 18.500. This data showed that there was 0.44 difference between the two groups. Further, the data showed that tcount < ttable (1.319 < 2.353). Hence, there was no significant difference between the two groups. Whereas, an analysis on the post-test data showed that the mean of the experimental group was 21.98 and the mean of the control group was 21.01. Thus, the post test result of the experimental group was higher than the control group. There was 0.96 difference between the groups. The T-test showed that tcount > ttable (3.264 > 2.353). Hence, there was a significant difference between the two groups. The post-test data analysis using t-test showed that the tcount was 3.264 and as the tcount > ttable (3.264 > 2.353), the null hypothesis (H0) was rejected. Thus, there was a significant difference between the story telling skill in the experimental group and the control group.